Utilization Of Caramunting Fruit As Natural Dyes Foods - Elly Jumiati, Mardhiana, Ira Maya Ab . (Universitas 17 Agustus 1945 Samarinda, 2017)
The rised of the existing food industry was not matched by the increase in the quality of products produced and the level of safety of materials used. So many of us encounter cases of food poisoning, both due to expired products and have been infected with harmful microorganisms or the use of harmful chemical or synthetic substances as food coloring.The study involved several processes and successive stages ranging from material preparation, phytochemical observation of extracts, screening of free radical capture activity, and antioxidant activity test extracts. Phytochemical observations of caramunting fruit extract included examination of phenol, flavonoid, and anthocyanin content. Making the extract is done by maceration.The results showed that the results of phytochemical test of fresh fruit and dried fruit karamunting is; (a) Antocyanin in fresh fruit was 0.65 mg CGE / g DW and dried fruit of 0.5 mg CGE / g DW, (b) total Phenol in fresh fruit was 15.05 mg GAE / g DW and dried fruit of 13.61 mg GAE / g DW, (c) total fresh fruit Flavonoids were 15.15 mg RE / g DW and dried fruit of 13.43 mg RE / g DW. The results of organoleptic tests of commercial syrup beverages and syrup given karamunting fruit extract (karamunting syrup) were (a) the sensory test results indicated that commercial syrup with colorant synthesis of color is preferred (score 6), preferred scent (score 5), preferred taste (score 4.8), preferred viscosity (score 5.6), (b) sensory assay results showed that syrup with karamunting fruit color / karamunting syrup of the color of most of the neutral panelists (score 4.3), as well as the scent (score 4.4), while the taste was favored (score 5.4), viscosity was alsopreferred(5,4).